Staging the West - Jeremiah Ariaz (Symphony in the Flint Hills, 2017)
Introduction: Kansas has been called the "Gateway to the West." As a visual artist I am interested in the West as both a location and a state of mind. Through various photographic projects, I have sought to draw attention to contradictions between factual and fictional depictions of the West and to contemplate the presence of this lore in contemporary culture.
Keywords: Staging the West; the West in contemporary culture; folklore; Chisholm Trail; Germany; festival; mythology of the West